Dampak Penggunaan Media Sosial terhadap Kesehatan Fisik Remaja di Desa Pene Lombok Timur - Buana, Maskar; Maulidin, Maulidin; Fitriatun, Erna; Irmansyah, Johan; Ramadhani, Africo (Discourse of Physical Education, 2026)
The increasing intensity of social media use among adolescents may affect physical health, particularly sleep patterns, eye health, and physical activity. This study aimed to describe the impact of social media use on adolescents’ physical health in Pene Village, Jerowaru District, East Lombok Regency. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. The study involved 12 informants, consisting of seven adolescents, two parents, and three village stakeholders selected using snowball sampling. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing. The findings showed that adolescents used social media intensively after school and at night. The physical impacts included late sleeping habits, morning drowsiness, eye fatigue, eye discomfort, reduced physical activity, and increased tiredness. The study concludes that social media use among adolescents should be managed through digital health education and family-based supervision.